Community Empowerment of Ponoragan Village, Loa Kulu District Through Education and Composing with The Takakura Method - Muhamad Dedy H; M. Alviansyah; Hansen Hansen (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Garbage is an object or material that is no longer used by humans so it is thrown away. The societal stigma regarding waste is that all garbage is disgusting, dirty, etc., so it must be burned or disposed of properly. All community activities always generate waste. Takakura is a household-scale composting method using the